Demand Functions for Condoms in Female Sexual Workers and Men who have sex with Men in India - Olivares, María (Compendium: Cuadernos de Economía y Administración, 2016)
This study explores the determinants of both the decision to purchase condoms and the actual demand for two samples of female sexual workers (FSW) and men who have sex with men (MSM) in India. Through the datasets collected by the Frontiers Prevention Project we obtained information for several cities where intervention programs were administered and for others that were taken as controls. As the free distribution of condoms is not random, we use a Heckman selection process for each sample. This strategy serves to evaluate public interventions based on free supply of condoms and promotion of HIV testing. On sexual workers it is found that the number of paying clients determines demand, but no significant effect is found from the number of condoms received for free. On men who have sex with men, in turn, the number of condoms received for free determines greater purchase.
Keywords: Selection bias, Heckman selection model, policy, HIV / AIDS.